Relationship between commodity market and Islamic stock market in Malaysia / Nor Fadhilah Mukhtar - Mukhtar, Nor Fadhilah (Faculty of Business and Management, 2016)
This study aims to investigate the relationship of commodity market to the Islamic stock market in Malaysia. The prices of three main commodities in Malaysia are selected, namely gold, crude oil, and crude palm oil, to examine how they affect the movement of Malaysian Islamic stock indices. This study employed the two models in Classical Linear Regression and studied the correlation coefficient to investigate the relationship and association between the independent variables and the dependent variable. The monthly price for gold, crude oil, and crude palm oil are collected from February 2007 until August 2015. FTSE Bursa Malaysia Emas Shariah closing price is collected for the same period to represent the Islamic stock market in Malaysia. The results show that there is positive relationship between crude palm oil price and the Islamic stock market. Apart from that, gold price is observed to have negative effect on the Islamic stock market. It is also found that all the prices of the selected commodities are associated with the Islamic stock indices, except for gold price. The reason for it may be due to the safe haven effect that exists in gold. These findings reveal that there is relationship between the commodity prices and FTSE Bursa Malaysia Emas Shariah indices. Therefore, the information furthers the understanding of the relationship between the commodity market and the Islamic stock market in Malaysia.